Revealing the Future of Graphology-Based Students (Handwriting Analysis) and E-Bookcreator-Based Learning in State MA Salatiga - Nurjadid (PT FORMOSA CENDEKIA GLOBAL, 2022)
The aim of this research is how to know earlier their personality, intelligent, etc. through hand writing analysis or graphology method. And then the using of e-smart application, namely e-book creator, the population in this research is the students of grade XI, which amounts 165 students, the method of this research is use the ADDIE development model (Analysis, design, development, implementation, evaluation) which aims to lead or achieve effective learning, as the basics of stages in a coherent manner (nuszewski & Molenda, 2008). There is progress the participation rate of the process of smart learning via Pra using e-book creator under 15% and Pasca using e-book creator more than 88%.